Characterization of three serotonin receptors from the small white butterfly, Pieris rapae. (August 2017) - Qi, Yi-xiang; Jin, Miao; Ni, Xu-yang; Ye, Gong-yin; Lee, Youngseok; Huang, Jia
Abstract: Serotonin (5-hydroxytryptamine, 5-HT) plays a key role in modulating diverse physiological processes and behaviors in both protostomes and deuterostomes. These functions are mediated through the binding of serotonin to its receptors, which are recognized as potential insecticide targets. We investigated the sequence, pharmacology and tissue distribution of three 5-HT receptors (Piera5-HT1A, Piera5-HT1B, Piera5-HT7 ) from the small white butterfly Pieris rapae, an important pest of cultivated cabbages and other mustard family crops. Activation of Piera5-HT1A or Piera5-HT1B by 5-HT inhibited the production of cAMP in a dose-dependent manner. Stimulation of Piera5-HT7 with 5-HT increased cAMP level significantly. Surprisingly, with the exception of 5-methoxytryptamine, agonists including α-methylserotonin, 8-Hydroxy-DPAT and 5-carboxamidotryptamine activated these receptors poorly. The results are consistent with previous findings in Manduca sexta . All three receptors were blocked by methiothepin, but ketanserin and yohimbine were not effective. The selective mammalian 5-HT receptor antagonists SB 216641 and SB 269970 displayed potent inhibition effects on Piera5-HT1B and Piera5-HT7 respectively. The results we achieved here indicate that the pharmacological properties of Lepidoptera 5-HT receptors are quite different from those in other insects and vertebrates and may contribute to development of new selective pesticides. This study offers important information on three 5-HT receptors from P. rapae that will facilitate further analysis of the functions of 5-HT receptors in insects. Graphical abstract: Highlights: Serotonin receptors Piera5-HT1A, Piera5-HT1B, and Piera5-HT7 from Pieris rapae were cloned and examined. Upon serotonin activation, Piera5-HT1A and Piera5-HT1B inhibited cAMP production whereas Piera5-HT7 induced it. All three receptors were poorly activated by serotoninergic agonists, indicating their distinct pharmacological properties. All three receptors were blocked by methiothepin; SB 216641 and SB 269970 inhibited Pr5-HT1B and Pr5-HT7, respectively. All three receptors were highly expressed in neuronal tissues while Pr5-HT7 mRNA predominated in the gut.